Grazing Lands and Biomass Management in Western Rajasthan Field Evidence - Jodha, N S (Annals of Arid Zone, 2016)
In a given ecological context a society evolves its two-way adaptation strategy involving adaptation (rationing) of the needs to resources as permitted by the natural resource base and adapting (developing/manipulating) natural resource base to meet increasing human needs. This process of dynamic nature- society interactions is illustrated with the emerging situation of grazing/fodder resources in the arid zone of western Rajasthan. The traditional strategies of farmers, including pastoralists, are becoming infeasible or ineffective in the changed demographic, institutional and technological context. Faced with increased pressure on grazing resources and their rising scarcity, new adjustments are being tried. The paper pleads for an understanding of these trends and for designing of range’management strategies accordingly. The paper draws on the farm and village level data collected at different times between 1963 and 1982.